Modeling Approach To the Long-Term Energy Demand and Energy Policy Implications Jyoti K Parikh - Planning Commission (Planning Commission, 1980)
This work deals with interaction of socioeconomic systems with energy demand systems. The energy sector claims for nearly 30% of the Plan allocations in the public sector. It was, therefore, necessary to initiate a modelling effort to look into the details of the energy sector and to identify policies for energy system management. As the implications of certain long-term policies are worked out here, this work augments the efforts for short-term planning by indicating what projections are desirable in the long run. In fact, a number of areas have been identified here where the formulation of the policies and also action-oriented plans are required in the Sixth Plan itself, if some of the long-term goals are to be achieved in 2000.
Government of India Planning Commission
Government of India Planning Commission